Self-assembly of coiled-coil fibrous proteins from elastomeric egg capsules of marine snails, busycotypus canaliculatus and pugilina cochlidium - Tay, Gavin Zhongcheng (2015)
The proteinaceous acellular egg capsules of Busycotypus canaliculatus and Pugilina cochlidium (a local marine snail species) possess excellent elasticity and mechanical damping ability. They exhibit remarkable extensibility that is fully, yet quickly, recoverable. This is unique and has been found to be related to protein secondary structure phase transitions from α-helix to β-sheet, instead of the more commonly observed entropic elasticity that dictates the rubber elasticity of amorphous bioelastomers such as elastin. Owing to such ability to absorb mechanical stress, it represents a desirable model system for the biomimetic engineering of highly resilient encapsulants for applications such as transplantation of delicate cells and tissues. The egg capsules of both species share many common features, both regarding their mechanical performance and hierarchical structures from the micro-scale down to the molecular level. In this study, the self-assembly process of the egg capsule proteins, which are secreted by the nidamental glands of the marine snails, and the structural hierarchy of the egg capsules are investigated to infer the structure-property relationships from the molecular to the macroscopic scale. The egg capsule proteins of both species are purified and analysed, and complete Pugilina cochlidium protein sequences are deduced from ribonucleic acid (RNA) transcripts. Fourier transform infrared (FTIR) spectra indicate that the egg capsule proteins are strongly α-helical in solution. In addition, circular dichroism (CD) spectra, together with matrix-assisted laser desorption and ionization time of flight (MALDI-ToF) mass spectra, suggest that the solubilised egg capsule proteins are capable of refolding into heteromeric α-helical coiled-coils from a denatured state. While the predicted locations of coiled-coil irregularities and domains varied within and between the species, primary sequence analysis suggests that all the egg capsule proteins have a propensity to form coiled-coils. These are in agreement with wide angle x-ray scattering (WAXS) and solid-state Raman and FTIR spectroscopic analysis of the mature egg capsules. The two species also displayed similarity in hierarchical organisation and a sub-micron fibril banding pattern of periodicity ~105 nm, as observed by atomic force microscopy (AFM), transmission electron microscopy (TEM) and small angle x-ray diffraction (SAXS). These observations support the view that there are common structural and hierarchical elements which are essential for the unique mechanical properties of the egg capsule.